Effectiveness of PMRY Scheme in India - Muthulakshmi, C. (Indian Journal of Finance, 2007)
The financial system is the lifeline of the economy. Banks are the backbone of the financial sector. They are the most dominant segment of the country's financial system. Banks plays a pivotal role in the development of a sound economy and form the core of the money market. It facilitates payment mechanism, mobilized insured deposits, act as credit intermediaries and serve as the principal channel for transmission of monetary policy actions to the economy at large. The banks provided financial assistance only to the Industries which had already established, financially sound, capacity to repay the loan, favourable credit guarantee etc. After the Independence in 1947, the Government of India as well as the State Governments was trying to show concern for the rural poor. The rural scenario in India was quite disturbing and needs much attention to eradicate poverty through employment opportunities. Therefore, the government had come up with different schemes to eradicate poverty. PMRY Scheme was announced and implemented in the VIIIth Five-Year Plan till now.